Paracervical block with 1% lidocaine for pain control during intrauterine device insertion: a prospective, single-blinded, controlled study - Cırık, Derya Akdağ; Taşkın, Elif A.; Tuğlu, Alper; Ortaç, Arzu Sümer; Dai, Ömer (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
In this prospective controlled study we aimed to investigate efficacy of paracervical block with 1% Lidocaine for pain control and demographic variables which may affect pain perception during intrauterine device insertion in Turkish women. Data from 95 women assigned to paracervical block (n=34), placebo (n=30) and no treatment (n=31) arms and asked to grade the pain level they felt during tenaculum placement, intrauterine device insertion and 5 minutes after the procedure using a visual pain scale. Demographic variables were also recorded. Pain scores were found to be lower in paracervical block group when compared to other 2 groups during tenaculum placement (p=0.00), intrauterine device insertion (p=0.00) and 5 minutes after the procedure (p=0.00). Level of pain was unrelated to mode of previous deliveries and current breastfeeding. Paracervical block is an easy, safe and effective way of pain control during intrauterine device insertion. Lack of vaginal birth history is not a reason to draw back from intrauterine device use.